Congenital hypogonadotrophic hypogonadism, induction of minipuberty, and future fertility - Stuckey, Bronwyn G A; Nolan, James D; Hurley, David M; Martin, Graeme B (Endocrinology, diabetes & metabolism case reports, 2023)
Summary A 33-year-old man with Kallmann syndrome had received pulsatile GnRH as an infant for the treatment of cryptorchidism. As an adult, his treatment for fertility with gonadotrophins was unusually rapid compared with expectations, with a total sperm count of 25 million after only 12 months of gonadotrophin therapy. We propose that pulsatile GnRH treatment as an infant induced minipuberty and facilitated his successful, rapid response to therapy. We also propose that identification of the absence of minipuberty in infants with clinical signs suggesting congenital hypogonadotrophic hypogonadism (CHH) is an opportunity for intervention with pulsatile GnRH yielding benefits for fertility decades later. Learning points Absence of minipuberty in males with CHH results in low Sertoli cell numbers and delayed response to induction of spermatogenesis in adulthood. Presentation with 'red flags' for androgen deficiency including cryptorchidism at birth, with or without micropenis, should prompt screening for CHH and minipuberty by measurement of gonadotrophins and testosterone in the first 2 months after birth. Pulsatile GnRH therapy in patients with CHH, given prior to age of attainment of Sertoli cell maturation, can replicate the normal physiology of minipuberty, thereby priming the testis for future fertility.